Adoption of improved processing technology among African locust bean processors in south-west, Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2020)
The paper investigated the effect of socio-economic and institutional factors on the adoption of improved locust bean processing technology in South-West, Nigeria. Specifically, the study described the socio-economic characteristics of the locust bean processors, examines the level of awareness and adoption of the improved locust bean processing technology in the study area and determines the effect of socio-economic and institutional factors on the adoption and intensity of use of improved locust bean processing technology in the study area. A multi-stage sampling procedure was used to select 360 respondents used for the study. The data were analyzed using descriptive statistics and the Cragg’s (double-hurdle) model. The result of the study showed that majority (84%) of the locust bean processors were female with an average age of 48 (±11.36) years. Majority (97%) of the respondents were married with an average household size of 8.25 (±4.32) persons. The result showed that 44.2% were aware while 55.8% were not aware of the technology in the study area. The results from the Cragg’s double hurdle model show that in the first hurdle, age, experience, access to credit and awareness positively influenced the decision to adopt the improved locust bean processing technology while in the second hurdle, education and income positively influenced the intensity of the use of the improved locust bean processing technology. It is therefore recommended that Relevant stakeholders, agencies and government should made available credit facilities which will enable the locust bean processors acquired the technology in no distant time.Int. J. Agril. Res. Innov. Tech. 10(1): 123-128, June 2020